Pelatihan Pengolahan Sampah Rumah Tangga Menjadi Pupuk Kompos dengan Metode Takakura di Krajan Pulung, Ponorogo - Ratnawati, Siti Rohmaturrosyidah; Saputri, Shela Mesyana (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This community service aims to enable the community to (1) sort and sort waste according to its type, (2) reprocess organic waste into compost using the composter method (takakura) while inorganic waste becomes tissue boxes and plant pots. The method used in this community service is the Asset Based Community Development (ABCD) approach, which prioritizes assets and potentials that are owned and around the community itself. The training activities were attended by 11 people and were further divided into several groups that focused on their respective tasks. The result of this activity is that some residents can (1 sort waste according to its type, and residents can sustainably (2) reprocess organic waste into compost using the composter method (takakura) while inorganic waste is reprocessed into tissue boxes for plant pots.